A study on weld morphology and periodic characteristics evolution of circular oscillating laser beam welding of SUS301L-HT stainless steel. (April 2023) - Zhao, Xu; Chen, Jintao; Zhang, Weihua; Chen, Hui
Highlights: Weld morphology characteristics of circular oscillating laser beam welding (OLBW) was illustrated; Variations of keyhole characteristics and molten pool morphology of circular OLBW were elucidated; Flow pattern of circular OLBW at distinct moments was described. Abstract: Many studies have identified the periodicity of oscillating laser beam welding (OLBW), but they do not provide a deep perspective to show the periodic changes of molten pool and keyhole characteristics. In the process of circular OLBW, the spatters were easily formed due to the unstable melt generated by rapid change in keyhole velocity, and its number was prone to decrease with the increase of frequency. The computational fluid dynamics (CFD) method successfully predicted the cross-section morphology of the weld, and the prediction deviation was small. In a single cycle, the fusion state between the newly generated melt and the existing molten pool determined the morphology of molten pool boundary, showing a 'W-U-W' shape change. The keyhole first destabilized and then stabilized again, and its depth exhibited a 'V' shape. The average flow velocity of the melt in the longitudinal section of the weld or keyhole center presented a 'W' shape. The keyhole depth or the average melt velocity period was equal to the oscillation period of circular OLBW.